Factors governing the tensile strength of basalt fibre. (April 2019) - Xing, Dan; Xi, Xiong-Yu; Ma, Peng-Cheng
Abstract: Basalt fibre has attracted great attention in developing fibre-reinforced polymers (FRP) in recent years. The tensile strength of basalt fibre is one of the most important considerations when formulating FRP structures. In this study, the strength of seven commercial basalt fibres was studied and compared, and the factors governing the strength of these fibres were investigated. The results showed that the strength of fibre is mainly dominated by the elemental composition of material and sizing on fibre surface, which functioning as "backbone" and "clothing" for the filament, respectively. Correlations between the tensile strength of fibre as a function of Al2 O3 content and Fe 3+ /Σ(Fe 3+ +Fe 2+ ) in the material were also established. Interestingly, as a processing step after fibre spinning, the sizing can increase the strength of material by up to 25%, illustrating the importance of such post-treatment for developing high performance basalt fibres.